THE EFFECT OF SOCIAL CAPITAL ON BUSINESS PERFORMANCE OF REDSELLER USERS ON REDSELLER LEADER BY ADIT WITH INNOVATION CAPABILITY AS A MEDIATION VARIABLE - Muhammad Rizky Nur Hafidhi; Muhammad Fajar Wahyudi Rahman (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the effect of social capital on the business performance of RedSeller Leader by Adit users with innovation capability as a mediating variable. This research is motivated by the phenomenon of fluctuating business performance among RedSeller users, indicated by unstable customer check-in numbers due to stagnant promotional strategies and intense competition among digital affiliates. This study employs a quantitative approach using a survey method involving RedSeller Leader by Adit users. The research data were analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) with the assistance of SmartPLS 4 software. The results indicate that: (1) social capital has a positive and significant effect on business performance; (2) social capital has a positive and significant effect on innovation capability; (3) innovation capability has a positive and significant effect on business performance; and (4) innovation capability mediates the relationship between social capital and business performance. These findings demonstrate that social networks, trust, and relationships among RedSeller users can serve as strategic resources when combined with the ability to create innovations in digital marketing and promotional strategies. Therefore, strengthening social capital accompanied by improving innovation capability is an important factor in enhancing the sustainable business performance of digital affiliate users.